2012
DOI: 10.1016/s1872-2067(11)60386-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of Steel-Making Slag and Carbons as Catalyst for Microwave-Assisted Dry Reforming of CH4

Abstract: The use of steel-making slag as catalysts for microwave-assisted dry reforming of CH4 was studied. Carbon materials (an activated carbon and a metallurgical coke), mixtures of carbon materials + Fe-rich slag and mixtures of carbon materials + Ni/Al2O3 were tested as catalysts. Mixtures of slag with carbons gave rise to higher and steadier conversions than those achieved over carbon materials. The case of mixtures with metallurgical coke was remarkably, changing from no conversion when coke was used alone to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…However, the system remained stable for both temperatures although at 700°C some minor deactivation was observed after 300 min. The same team reported on the utilization of slags from steel making combined to two different carbonaceous materials (activated carbon and metallurgical char) as catalyst for a microwave-assisted dry reforming reaction (Bermudez et al, 2012 ). The authors mentioned that the slags alone were not reactive toward microwave and could not be used without any support.…”
Section: Other Conversion Approachesmentioning
confidence: 99%
“…However, the system remained stable for both temperatures although at 700°C some minor deactivation was observed after 300 min. The same team reported on the utilization of slags from steel making combined to two different carbonaceous materials (activated carbon and metallurgical char) as catalyst for a microwave-assisted dry reforming reaction (Bermudez et al, 2012 ). The authors mentioned that the slags alone were not reactive toward microwave and could not be used without any support.…”
Section: Other Conversion Approachesmentioning
confidence: 99%
“…The promotional effects of different carbonaceous species, i.e. metallurgical coke (CQ) and coconut shell-derived activated carbon (FY5), on the catalytic performance of steel-making slag (eFe) catalysts for microwave-assisted DRM were evaluated by Bermudez et al (2012) at 800 °C and the stoichiometric feed composition. Comparable to the findings of Fidalgo et al (2011), they found that mixture of Fig.…”
Section: Mixing Metal Catalysts With Microwave-absorbing Materialsmentioning
confidence: 99%
“…Reprinted from Odedairo et al (2016), Copyright (2015, with permission from Elsevier steel-making slag (eFe) and coconut shell-derived activated carbon (FY5) exhibited greater and steadier catalytic activity with time-on-stream compared to those attained using activated carbon alone. Bermudez et al (2012) also conducted microwave-assisted DRM over a mixture of carbon + steelmaking slag and carbon + Ni/Al 2 O 3 at various VSHV in order to examine their catalytic activity with different metals. They discovered that the reactant conversions over carbon + Ni/Al 2 O 3 catalyst was independent from VSHV.…”
Section: Mixing Metal Catalysts With Microwave-absorbing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, microwave (MW) irradiation has attracted attention as a tool for regeneration due to its capability of molecular-level heating. Interesting reports have appeared on the application of MW-heating technology for regenerating AC (Price and Schmidt 1997;Bradshaw et al 1997;Coss and Cha 2000;Liu et al 2004;Jones et al 2002;Deming et al 2011;Guido et al 2008;Bermudez et al 2012) with very promising results. Applications of microwave regeneration technologies are lagely used in industries for economical purposes (Remya and Lin 2011).…”
Section: Introductionmentioning
confidence: 99%